Growing food under difficult conditions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Amaranth to zai holes: ideas for growing food under difficult conditions by Laura Meitzner and Martin Price, 1996 404pp US$29.95 + shipping ISBN 0 9653360 0 X